Simultaneous Biaxial Stretching of Polypropylene Resins of Varying Tacticity Part II: Film Morphology and Properties - Capt, L.; Rettenberger, Stefan; Münstedt, Helmut; Kamal, M. R. (International Polymer Processing, 2022)
The simultaneous biaxial stretching behavior of three Ziegler-Natta-based isotactic polypropylene resins of varying isotacticity was studied using a laboratory film stretcher that simulates closely stretching conditions encountered in the commercial process. The effect of isotacticity on the final morphology and end film properties was associated with the effect of isotacticity on the thermal properties of the resin. The results showed that the degree of undermelting, oT(um) = T-m-T, determines the phase composition of the polymer before stretching and the morphology and orientation of the stretched films. The size and orientation of the crystallites in the stretching plane is mostly determined by the degree of undermelting. The elongation at break was correlated with the residual crystallinity of the film before stretching, and the elastic modulus was correlated with the final degree of crystallinity and the density of tie chains.
CRIS-Team WoS Importer:2022-03-25